The powerful ideas of making: Building beyond the curriculum - Nathan Holbert (Journal of Innovation and Entrepreneurship, 2016)
In this paper, rather than consider how fabrication technologies and maker activities can be directly matched to existing standards or allow for more efficient content coverage, I position making as a network of powerful ideas and perspectives that are highly connected to other ideas, personal and syntonic to the learner, and are immediately useful for solving problems of personal importance. Furthermore, I argue that creating learning environments where learners encounter and take ownership of these powerful ideas requires instructors, coaches, administrators, and designers that are committed to creating space for the learner to make meaningful choices, to tinker and explore, and to collaborate. Bots for Tots, a project that engages children in making toys for members of their community, is briefly described to highlight the affordances and challenges of implementing design features that focus on engaging learners with powerful ideas.
Keywords: 650; Constructionism; Making; Fabrication; Powerful ideas; Design